Retinal blood flow measurement with ultrahigh-speed swept-source / Fourier domain optical coherence tomography - Baumann, Bernhard; Potsaid, Benjamin; Liu, Jonathan J.; Kraus, Martin; Huang, David; Hornegger, Joachim; Duker, Jay S.; Fujimoto, James G. (Ophthalmic Technologies XXI, 2011)
Doppler OCT is a functional extension of OCT that provides information on flow in biological tissues. We present a novel approach for total retinal blood flow assessment using ultrahigh speed Doppler OCT. A swept source / Fourier domain OCT system at 1050 nm was used for 3D imaging of the human retina. The high axial scan rate of 200 kHz allowed measuring the high flow velocities in the central retinal vessels. By analyzing en-face images extracted from 3D Doppler data sets, absolute flow for single vessels as well as total retinal blood flow can be measured using a simple and robust protocol. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).